(untitled) (Archive of Conferences, 2022)
in this article the pedagogical conceptual essence of preparing students for the organization of spiritual and enlightenment work in the process of professional and pedagogical education and ways of pedagogical impact on the historical development, spiritual and enlightenment perfection, the organization of spiritual and enlightenment work with students illuminated by.